THE THEORY OF FISCAL FEDERALISM AND THE RUSSIAN PRACTICE - N. G. Ivanova (Финансы: теория и практика, 2017)
The efficiency of the system of inter-budget relations in any country largely depends on how it conforms to fundamental principles of the fiscal federalism that were given a deep theoretical insight by foreign and Russian economists. The construction of the fiscal federalism model in Russia has been going at a slack pace due to objective difficulties of its implementation in the huge country with unevenly developed areas. At the same time, problems and contradictions that have by now accumulated in the practice of inter-budget relations have serious social and economic implications. The conclusion made in the paper substantiates the necessity of improving the current mechanism of inter-budget transfers, particularly, increasing the proportion of unconditioned transfers and reforming the procedure for granting federal subsidies. The authors propose some measures for overcoming the present crisis of sub-national budgets and ways to strengthen the tax potential of the Russian Federation.